Quality of experience key metrics framework for network mobility user - Noor, Rafidah Md; Khorsandroo, S. (Academic Journals, 2011)
This paper presents a new framework of Quality of Experience (QoE) in mobile network. The user acceptance of a mobile application depends on the applications perceived QoE. Currently, there is no comprehensive framework which integrates QoE and Quality of Service (QoS). The components of framework consist of the network mobility users, traffic classification matrixes and QoE key metric. The performance evaluation of this framework for assessing QoE in service class and user class model is presented. The simulation results demonstrate the user satisfaction evaluated by the achieved QoE at different service classes and user classes. The new QoE score model can give deeper understanding of the mobile user interaction within the mobile environment; quantify the users QoE and their relationship with QoS.